Adult-onset autoimmune-type enteropathy: potential relationship to an adverse drug reaction. Issue 1 (2nd December 2019) - Chetty, Runjan; Cino, Maria; Okrainec, Allan
Abstract : Objective: To describe an example of adult-onset autoimmune enteropathy (AIE) that coincided with drug-induced reaction. Design: A 54-year-old patient was presented with Stevens-Johnson syndrome after a course of quinolones. This was followed shortly thereafter by epigastric pain, diarrhoea and weight loss. She also developed an autoimmune neutropenia. Results: Several biopsies were performed from the upper and lower gastrointestinal tract (GIT). The duodenal biopsies showed intraepithelial lymphocytosis; therefore, coeliac disease was considered. However, confirmatory serology was negative and the patient did not respond to a gluten-free/gliadin-free diet. Both upper and lower GIT biopsies consistently showed an absence of goblet cells resembling the changes of an AIE. Conclusion: This is an unusual case of autoimmune-pattern enteropathy in an adult that was potentially drug-induced.